ReCab a proposed post-rehabilitation development for the former Cabanatuan City dumpsite through Integrated Landscape Approach - Esmino, Hazel Grace Restua; Navarra, Nappy L. (Quezon City College of Architecture, University of the Philippines Diliman, 2023)
The utilization of open dumpsites poses significant risks not only to human health but also to the biodiversity of an area. The presence of external factors like changes in land cover and harmful human activities further compounds these threats. To address these issues, the rehabilitation of dumpsites and the implementation of sustainable landscape development are imperative. Cabanatuan City, as the most populous city in Nueva Ecija, is particularly susceptible to pollution. The existence of a former open dumpsite in the city led to an increase in illegal dumping, endangering the health of nearby residents and diminishing land economic value. Fortunately, the dumpsite has been closed and is now being considered for development as a prominent attraction in Cabanatuan City. Hence, this study was conducted to provide a landscape development plan and guidelines for the most feasible and sustainable development option.
The study adopts an Integral Landscape Approach as its foundation, integrating theories to formulate hypotheses for analyzing stakeholder's landscape preferences. Through habitat integrity analysis, it was determined that the site can be developed. Stakeholders data was subjected to deductive analysis. Three scenarios including biodiversity park, ecological park, and agricultural technology park were selected based on ranking activity derived from expert consultations. Through a series of assessments considering sustainability and stakeholder preferences, the ecological park emerged as the most favorable option. A feasibility assessment, including budgetary estimates, ensured the project's viability. The study presents principles, elements, and guidelines supported by relevant theories, offering a feasible and elements, and guidelines supported by relevant theories, offering a feasible and sustainable landscape development plan for the former dumpsite.
include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Integrated Landscape Approach; Rehabilitation; Sanitary landfills -- Cabanatuan City; Sustainable development -- Cabanatuan City